Literature and ICTE: Issues and Perspectives - Zine El Abidine, Mohammed; Nejjari, Amel; Khaldi, Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Throughout the undulating course of history, literature has remained a steadfast companion to the pursuit of language instruction, defying the ebb and flow of its prominence. Presently, it is experiencing an extraordinary renaissance, and to effectively reintegrate it within language classrooms and ignite learners' enthusiasm, digital technologies have emerged as an invaluable ally. The purpose of this article is to embark on an exploration of the multifaceted role of literature within diverse language teaching methodologies while delving into the intricate interplay between literature didactics and the realm of Information and Communication Technologies (ICT). We endeavor to elucidate the notion that digital technology, when wielded as a pedagogical instrument, serves as a veritable fount of innovation in the domain of language and culture instruction, holding immense potential to invigorate learners' motivation.